STRATEGY AND RISKS REFORMING THE ELECTRICITY MARKET IN THE REGIONS OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. Competitiveness implies a free choice of suppliers by consumers, absence of barriers to the market of supply and sale. The new European format of the electricity market model creates new challenges and threats to the functioning of electricity market enterprises in terms of transparent and objective conditions for access to consumption and operation of electricity networks, unbiased accelerated development of the electricity market to the dynamics of the economic system. Reforming the electricity market combines the processes of achieving organizational, economic, technical, social, and environmental goals. However, this combination has different consequences and risks associated with minimizing costs. Clarification of long-term goals and objectives requires a comprehensive approach to the analysis of the electricity market in the following areas: the formation of reform priorities, outlining the benefits and risks, assessing the likely risks of the environment.The purpose of the article. The purpose of this article is to determine the most optimal strategy and the most probable risks that may arise in the processes of formation of the electricity market both in the regions of the state and nationwide.Results. One of the most important problems of the system operator in ensuring its independence and mutual respect for all market participants. To this end, the following measures are legally justified: procurement of related services on a competitive basis; transparent information of the available list of related services, their volumes, cost, terms, and requirements to suppliers; formation of accounting for the cost and revenue component in the implementation of the centralization of dispatch management from other activities; formation of access to the capacity of interstate electric networks by conducting electronic auctions; submission of the UES development plan to the Cabinet of Ministers of Ukraine for consideration even in case of disagreement of the interesting instances. However, strengthening the role of the system operator does not ensure its complete independence from external risks. Liberalization of the electricity market takes into account the availability to the wholesale market of other participants who can directly enter into agreements with generation companies and sell electricity to the retail market. Such participants are usually large industrial consumers. At the same time, the retail market is creating a so-called competitive environment, which is an alternative to the existing "oblenergo". The formation of consumer choice will further affect the price and quality and transparency of competitive relations.Conclusions. The investment component of the region will grow only if the electricity market is reformed. However, the processes of introduction of a new model of the electricity services market are formed in a short time, the introduction and adoption of legislation, the implementation of organizational and structural changes, software testing. Nevertheless, the processes of reforming the electricity services market are an integral attribute of the region’s integrated investment policy.
Keywords: electricity market, market environment, electricity resource, integrated energy system.